Nilai-Nilai Islam Moderat dalam Pembelajaran PAI pada Masa Pandemi Covid19 Di SMK Negeri 1 Kebumen - Agus Salim Chamidi (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
This qualitative research aims to determine the process of cultivating moderate Islamic values ​​in the learning of Islamic Religious Education (PAI) in Class X at SMK Negeri 1 Kebumen and to determine its success. Data collection was carried out through observation, interviews, and documentation using descriptive-analytic analysis techniques. The research informants were Class X Islamic Education teachers and other related informants. The research was conducted in August-October 2020 during the Covid19 pandemic. The results of the research are that: (1)during the Covid19 pandemic the process of cultivating moderate Islamic values (wasathiyah) regarding al-adl (justice), al-tawazun (balance), and al-tasamuh (tolerance) continues in the X-Class on PAI Learning at SMK Negeri 1 Kebumen according to curriculum guidelines balanced with teacher creativity in incorporating these concepts and values ​​from the start of making lesson plans to the learning evaluation process, (2)the success of planting moderate Islamic values ​​is reflected in the results of the evaluation of learning and participant behavior Class X students of SMKN 1 Kebumen.